DEVELOPMENT OF A BACKHAND SKILL TEST FOR BADMINTON PLAYERS - Singh, Bhopinder; Bhushan , Ekta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores the development of a comprehensive test to assess backhand shot skills in badminton. Initially inspired by a personal shift from track and field to badminton during undergraduate studies at the Indira Gandhi Institute of Physical Education and Sports Sciences, the study focuses on the influence of legendary players, particularly Taufik Hidayat’s backhand technique. The research aims to design a standardized test that evaluates the key components of a well-executed backhand shot, incorporating both qualitative and quantitative measures. The test assesses technical elements such as shot placement, accuracy, and consistency, while also considering broader aspects of player performance. Grounded in research methodologies from prior studies on badminton skill assessment, this test was developed through multiple stages, including content validation by experts, field testing, and iterative revisions. The final instrument underwent thorough validation using Lawshe’s Content Validity Index (CVI) method, achieving an "Excellent" rating. By increasing the number of shot attempts from 12 to 16 and refining the scoring zones on the court, the test ensures a more accurate evaluation of a player’s backhand skill and precision. This tool offers valuable insights for coaches and trainers, enabling targeted improvement in player performance and contributing to the broader field of badminton training.